If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(m + -11) = 13 Reorder the terms: -1(-11 + m) = 13 (-11 * -1 + m * -1) = 13 (11 + -1m) = 13 Solving 11 + -1m = 13 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1m = 13 + -11 Combine like terms: 11 + -11 = 0 0 + -1m = 13 + -11 -1m = 13 + -11 Combine like terms: 13 + -11 = 2 -1m = 2 Divide each side by '-1'. m = -2 Simplifying m = -2
| 100=-(x+8)+2x | | 3(2z-3)=5(z+2) | | 2(9x)+2(2x)=484 | | 7(5x+13)=301 | | 2/3x=-1/2 | | 3w+4+2w=-26 | | (1)/(5p2)*(5p3-35p2)/(9p-36) | | X(2)+2x=23 | | 5x+2=9x-22 | | w/7+2=5 | | 5(-9x+15)=-195 | | x=450-.5y | | 3k+16=5 | | 7x^-3/16x^-1 | | 5(-9+15)=-195 | | x+(s+40)=180 | | 4x+2(3x-7)=6-(4-x) | | 3(6m)+m=21m | | 7(5x+16)=-203 | | 12y-7=53 | | -26x-2x=10-8x | | 4x^2+-10x+25=0 | | 2(x)+y=900 | | 10(-10x+12)=-380 | | 4x^2-10x+25=20 | | 5x^2-20=4 | | (5x+15)/(3x+9) | | 5x+15/3x+9 | | 3/7=x | | -5(9x+12)=-375 | | 1x-11x+8=88 | | (2x^2+3x-4)-(4x^2-7x+1)= |